Combined Fingerprint Template Based Revocable Session Key Generation - S.MEENAKSHI, HEMA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Ensuring network and information security is one of the top most concerns related to data transmission. Cryptography is most effective solution for secure data transmission. Efficient cryptographic method depends on cryptographic key and its management. Traditional cryptography faces many problems such as difficulty in memorizing random keys and key storage in network. Linking biometric traits of a person with cryptography overcomes these limitations. Different biometrics that can used are fingerprint, iris, face etc. To address the limitations, biometric and cryptography is combined to develop Crypto Biometric Systems which uses biometric traits to protect or generate the cryptographic key. But key generation based on biometric has problems with privacy of biometrics and revocability of biometric. Hence, there is a need to generate an efficient cryptobiometric system which satisfies privacy and revocability of biometric data. This paper is to generate crypto-biometric key from cancellable fingerprint template of both users participating in the communication. Cancellable transformation is performed based on triangulation feature set construction to ensure privacy of fingerprint template. Cancellable fingerprint templates of both sender and receiver are safely transmitted to one another using LSB steganography. Fusion technique at feature level is used in concatenation of both templates to create a combined template. Combined template elements are shuffled using shuffle key and applying hash on the shuffled element set generates the unique session key. To add revocability and key diversity shuffle key update phase is implemented. Increasing security demands shifted the focus from single biometrics to multibiometrics. In this method, multiple fingerprints of a user is used for key generation which overcomesandresolvesissuesinsinglebiometricsystems.